FILIPPO SASSETTI (1540-1588), A FLORENTINE AT THE SERVICE OF THE GREAT NAVIGATIONS: COMMENTED AND ANNOTATED TRANSLATION FROM ITALIAN TO PORTUGUESE OF THE CHART XCV - Simoni, Karine; Ribeiro, Karla (Revista de Letras, 2023)
On his trips to Portugal, Spain and the Indies, which he carried out between 1578 and 1581 in the service of the Medici family, from Florence, the Florentine merchant Filippo Sassetti (1540-1588) also dedicated himself to writings that compiled an epistolary of about 126 missives (Boutier, 1994) addressed to friends, family and authorities. The purpose of this article is to make some considerations on Sassetti's writing, based on the annotated and commented presentation of the translation from Italian into Portuguese of the letter XCV, considerations that will serve as a guide for the translation of the whole epistolary. This letter was written from Cochin, India, in 1585 and submitted to Michele Saladini, merchant of Pisa. The numbering of the letter follows the edition published in 1855 by Ettore Marcucci, and was chosen for being one of the twelve letters in which the author cites Verzino, the name by which Brazil was known on the Italian peninsula at the time of the Great Navigations. The study has the following structure: biographical-critical presentation of the author (Dei, 1995; Brege, 2014; 2020); reflections on the writing of letters and travel literature, exposition of the main themes and recipients present in the letters and, finally, the translation and comments of the letter XCV. The translation and comments were made from the considerations of Torres (2017) on commented translation, and Berman (2013), Venuti (2019) and Eco (2014) on translation and translation studies. The translation comments will deal with situations related to temporal markers, such as forms of treatment, lexical and stylistic-syntactic issues.